Alteration of N6 -Methyladenosine mRNA Methylation in a Rat Model of Cerebral Ischemia–Reperfusion Injury - Yi, Dazhuang; Wang, Qunhui; Zhao, Yuhao; Song, Yu; You, Hong; Wang, Jian; Liu, Renjie; Shi, Zhongqiang; Chen, Xuan; Luo, Qi (Frontiers in Neuroscience, 2021)
Aim This study was conducted in order to reveal the alterations in the N6-methyladenosine (m6A) modification profile of cerebral ischemia–reperfusion injury model rats. Materials and Methods Rats were used to establish the middle cerebral artery occlusion and reperfusion (MCAO/R) model. MeRIP-seq and RNA-seq were performed to identify differences in m6A methylation and gene expression. The expression of m6A methylation regulators was analyzed in three datasets and detected by quantitative real-time polymerase chain reaction, western blot, and immunofluorescence. Results We identified 1,160 differentially expressed genes with hypermethylated or hypomethylated m6A modifications. The differentially expressed genes with hypermethylated m6A modifications were involved in the pathways associated with inflammation, while hypomethylated differentially expressed genes were related to neurons and nerve synapses. Among the m6A regulators, FTO was specifically localized in neurons and significantly downregulated after MCAO/R. Conclusion Our study provided an m6A transcriptome-wide map of the MACO/R rat samples, which might provide new insights into the mechanisms of cerebral ischemia–reperfusion injury.